المرأة الجزائرية المعاصرة بين خطاب التقليد والحداثة - حجال, سعود; بلحاجي, محمد (Changement Social; No 4 (2018): revue change social, 2018)
كانت المرأة الجزائرية ولازالت موضوعا لكثير من الدراسات السوسيولوجية والانثروبولوجية والتي رصدت تقاليدها وأعرافها وطقوسها ورمزياتها، محاولة تحديد خصوصيتها على مستوى الهوية والتمـايز،. ابتدأت مسألة حداثة المرأة الجزائرية مع انطلاق الإصلاحات الكبرى التي شهدتها الجزائر، ووجدت صدى وترحابا من طرف المفكرين الذين دعوا إلى تحررها من التقاليد العتيقة وتحفيزها على المشاركة في الأمور العلمية والسياسية أسوة بالرائدات السياسيات والعالمات في البلدان الفتية المماثلة للجزائر.بالمقابل ينظر التيار المحافظ إلى المرأة الجزائرية بطرح مخالف إن لم نقل في بعض الأحيان مناقض للرؤية الحداثية كونه يركز على الخصوصية الثقافية المحلية التي ينبغي المحافظة على هويتها وليست بالضرورة معرقلة لتحرر المرأة ولا لتخلفها داعية بدلك إلى جعل المرأة عنصرا فاعلا في عملية التنمية في إطار الأصالة و المعاصرة . Abstract : Algerian women have been the concern of many sociological and anthropological studies, which have identified their traditions, customs, rites and symbols, trying to define their specificity at the level of identity and differentiation. Women's discourse has taken an important place as the public discourse has revived from common representations in the community. The issue of Algerian women modernity has begun with the launching of major reforms in Algeria. It was welcomed and encouraged by intellectuals who called for their liberation from ancient traditions and encouraged them to participate in scientific and political matters, same as the political and scientific leaders in the young countries similar to Algeria ,On the other hand, the conservative trend regards the Algerian woman as presenting a dissent, if not at times contradictory to the modernist vision, because it focuses on local cultural specificity, which should be preserved and not necessarily a hindrance to women's emancipation or backwardness, calling for women to be active in the process of development within the framework of originality and Contemporary